2014
DOI: 10.1186/2049-1891-5-39
|View full text |Cite
|
Sign up to set email alerts
|

Effects of magnesium on the performance of sows and their piglets

Abstract: The objective of this study was to evaluate the effects of supplemental magnesium (Mg) on the performance of gilts and parity 3 sows and their piglets. Fifty-six gilts (Trial 1) and 56 sows (Trial 2) were assigned to one of 4 treatments according to their mating weight, respectively. The treatments comprised corn-soybean meal based gestation and lactation diets (0.21% magnesium) supplemented with 0, 0.015, 0.03, or 0.045% Mg from mating until weaning. The results showed that magnesium supplementation significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 11 publications
3
16
0
Order By: Relevance
“…Whilst there was no impact of MgSO 4 supplementation on inter-piglet birth intervals, the total farrowing duration was increased in this treatment. The laxative effect of MgSO 4 is well documented, and its dietary inclusion has been shown to reduce the incidence of constipation in sows [ 15 ]. Constipation is commonly associated with an increased farrowing duration [ 16 ], and so it might have been reasonable to expect a shorter length of parturition in Mg sows.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst there was no impact of MgSO 4 supplementation on inter-piglet birth intervals, the total farrowing duration was increased in this treatment. The laxative effect of MgSO 4 is well documented, and its dietary inclusion has been shown to reduce the incidence of constipation in sows [ 15 ]. Constipation is commonly associated with an increased farrowing duration [ 16 ], and so it might have been reasonable to expect a shorter length of parturition in Mg sows.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteroides were known to metabolize oligosaccharides of host origin derived from mucins [ 41 ], which were predicted to transport oligosaccharides across the outer membrane. Bacteroides were also reported to produce both propionate and succinate as terminal products of its metabolism [ 42 ]. Furthermore, propionate could not only create an acidic environment but also decreased the expression of virulence factors of pathogens [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the requirement for Mg can be met by common feed ingredients in animal diets, research and practice have shown benefits from supplementing Mg above the estimated minimum requirements in several food producing animals like pigs, poultry, and cows (as farm ruminants’ representative). The practice of supplementing feedstuffs with Mg is widely used, with the primary aim to avoid Mg deficiency and then to improve animal performance (fertility and yield) and sometimes products’ quality [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Mg In Farm Animals’ Dietmentioning
confidence: 99%
“…The reproductive performance of high producing sows has increased dramatically over the past decades, which may contribute to the changes in their nutritional requirements. It has been proven that Mg supplementation improves the conception rate of sows by 11–15% [ 10 ]. Moreover, its supplementation significantly reduces the weaning to oestrus interval in gilts and enhances the total number of born piglets, born alive, and weaned.…”
Section: Mg Supplementation In Pig Nutritionmentioning
confidence: 99%